Effects of the combination of red yeast rice-containing commercial Chinese polyherbal preparation with statins for dyslipidemia: a systematic review and meta-analysis - Shi, Menglong; Sun, Tianye; Zhang, Chenyao; Ma, Yucong; Pang, Bo; Cao, Lujia; Ji, Zhaochen; Yang, Fengwen; Zhang, Junhua (Frontiers in Pharmacology, 2024)
Background: Significant challenges are associated with the pharmacological management of dyslipidemia, an important risk factor for cardiovascular disease.Limited reliable evidence exists regarding the efficacy of red yeast rice (RYR)-containing commercial Chinese polyherbal preparation (CCPP), despite their widespread use in China.We aimed to investigate the efficacy of RYR-containing CCPPs combined with statins in treating dyslipidemia.: Eight databases were searched for relevant randomized controlled trials (RCTs) from database inception date to November 2023. Outcome measures, including low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), triglyceride (TG), clinical efficacy, and adverse reactions, were assessed. The Cochrane Handbook for Systematic Reviews of Interventions was used for quality evaluation, and the meta-analysis was conducted using RevMan 5.3 and Stata 15.1. Results: Thirty-three studies involving 4,098 participants were included. The combination of RYR-containing CCPP, such as Xuezhikang (XZK), Zhibitai (ZBTAI), or Zhibituo (ZBTUO) with statins had a significant effect on the increase in clinical efficacy [RR:1.16, 95%CI (1.13, 1.19), P<0.00001]. In addition, they also improved blood lipid profile parameters by increasing HDL-C levels [MD:0.21, 95%CI(0.17, 0.25), P<0.00001], and decreasing TC [MD:-0.60, 95%CI(-0.76, -0.45), P<0.00001], TG [MD:-0.33, 95%CI(-0.39, -0.26), P<0.00001] and LDL-C levels [MD:-0.45, 95%CI(-0.54, -0.36), P<0.00001]. No significant adverse reactions was observed in the RYR-containing CCPPs. Notably, ZBTAI and XZK significantly reduced the incidence of gastrointestinal disturbances and muscular adverse reactions. However, subgroup analyses suggested that the type of CCPPs, dose, and treatment duration might affect the efficacy of RYR-containing CCPPs. Conclusion: RYR-containing CCPPs combined with statins appears to improve lipid profiles and clinical efficacy in patients with dyslipidemia. However, due to the poor quality of the included studies, and some studied showing negative findings was unpublished. The results should be interpreted with caution until further confirmation by well-designed RCTs.